Pemanfaatan Ikan dan Hasil Laut sebagai Sumber Gizi dalam Tradisi Masyarakat Pesisir Aceh - Afifah Ramadhini; Abubakar; Cut Nya Dhin; Fitriatun Nisa; Gustika Rohaya; Izziya Kamila; Nadjwaa Arabiya; Vina Silvia; Sonia Ismah; Yeni Shofia (Jurnal Sociohumaniora Kodepena (JSK), 2026)
Aceh is one of the coastal regions in Indonesia with abundant marine resources. Fish and other seafood play a significant role not only as a primary food source but also as part of the cultural traditions of coastal communities. This study aims to analyze the role of fish and marine products as nutritional sources and their relationship with the traditions of coastal communities in Aceh. The research employs a qualitative approach using a literature review method based on various scientific journals and research reports related to coastal communities, marine resource management, and fish consumption patterns. The findings indicate that fish is a high-quality source of animal protein containing essential nutrients such as omega-3 fatty acids, vitamins, and minerals that contribute to human health. In Acehnese coastal communities, seafood is also closely associated with social and cultural practices, including traditional ceremonies and communal meals. Local wisdom and traditional institutions such as Panglima Laot regulate fishing activities and marine resource utilization to ensure sustainability. Therefore, fish and marine products play a crucial role not only in improving nutritional status but also in maintaining cultural identity and environmental sustainability among coastal communities in Aceh.